PEMANFAATAN ABU CANGKANG KERANG SEBAGAI BAHAN TAMBAH DALAM CAMPURAN BETON - Mulyati, Mulyati; Rahmi, Soemi; Syafitri, Ayu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to examine the use of shell ash as an additive in concrete mixtures to improve the quality of concrete. The shells used in the research were the lokan and pensi species. Shell ash is obtained through a burning process until it becomes powder and is crushed until smooth. Addition of shell ash into the concrete mixture with percentage variations of 0%, 1%, 2%, 3%, and 4% of the weight of the cement. Concrete mix planning uses SNI 7656:2012 for a planned compressive strength at 28 days of 20 MPa. Compressive strength testing was carried out at 28 days of concrete age to evaluate the effect of adding shell ash on the compressive strength of concrete. The results of the study showed that the addition of up to 4% shell ash can increase the workability and compressive strength of concrete. The addition of 3% of lokan shell ash produced a maximum compressive strength of 24.02 MPa, an increase of 15.70%. Thus, shell ash has the potential to be used as an alternative additive in making concrete, especially the lokan species.Keywords: lokan shell ash, pensi shell ash, additives, concrete, compressive strength